Penyusunan Tarif PNBP untuk Layanan Reuse dan Recycle Sumber Radioaktif Tertutup Limbah Radioaktif Tidak Terpakai di Unit Instalasi Pengolahan Limbah Nuklir BRIN - Handayani, Widya; Karunia, R. Luki; Sutrisno, Edy (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The financial report on the management of Non-Tax State Revenue (PNBP) for radioactive waste reuse and recycling services for Radioactive Substances has irregularities. The aim of this research is to analyze the conditions required in preparing rates and types of PNBP so that this service can be proposed as a service with fixed fees and a legal umbrella for better management and supervision of public services and PNBP. Based on the use of applied research methods with a qualitative approach, it was found that the basis for considering the preparation of tariffs for this service is transparency, fairness, responsive-ness, simplicity, timeliness and certainty. The result of the tariff calculation using the ABC method is Rp. 26,736,329,- obtained based on the real needs for each service delivery activity. The results of the volume effectiveness analysis were 5.6 and the service revenue performance was 378.76 percent, considered very effective and performing well.